Image Representation Of Men In Tokopedia X BTS Advertising: Waktu Indonesia Belanja - Herrawati, Sri; Ritonga, Muhammad Husni; Zuhriah (International Journal of Cultural and Social Science, 2022)
This research is entitled "The Representation of Male Image in Tokopedia X BTS Advertisement: Indonesian Shopping Time". The purpose of this study is to find out how the meaning of denotation and connotation contained in the advertisement and how the meaning of the image of men in the advertisement of Tokopedia X BTS: Indonesian Shopping Time is. The theory used in this research is Representation Theory. The object of this research is Tokopedia's video advertisement. This study uses Roland Barthes' semiotic analysis method in which researchers can better understand the meaning of denotation, connotation, and the meaning of male images in Tokopedia advertisements through expressions, body language, clothing, and taking pictures from the Tokopedia advertising model. The findings from the research that has been done regarding the image of men in Tokopedia advertisements are that men are depicted with clean white faces, tall, and graceful. The end of the 1900s to the 2000s a new term emerged, namely the new masculinity. With this, it presents a unique and interesting blend that can open the world's eyes to the stereotypes about the masculine imagination that have been formed for a long time. Where men used to emphasize muscle, power, and disorganized style. Compared to today's men like Tokopedia's advertising models, the image displayed is friendly, stylish, unrelated to violence, and sensitive to the feelings around them.